Clinical Phenotyping and Biomarkers in Spinal and Bulbar Muscular Atrophy - Millere, Elina; Rots, Dmitrijs; Glazere, Ieva; Taurina, Gita; Kurjane, Natalja; Priedite, Viktorija; Gailite, Linda; Blennow, Kaj; Zetterberg, Henrik; Kenina, Viktorija (Frontiers in Neurology, 2021)
Background. Spinal and bulbar muscular atrophy (SBMA) or Kennedy disease [OMIM: 313200] is a rare X-linked neuromuscular disease. Patients commonly present with muscle cramps, tremors, leg weakness, dysarthria and dysphagia. Methods. We deeply phenotyped and evaluated the possible extent of affected systems in all patients with SBMA in Latvia (n = 5). In addition, neurophysiological studies and blood analyses were used to perform a molecular diagnosis and evaluate biochemical values. We analysed neurofilament light (NfL) as a possible biomarker. Results. Neurological examination revealed typical SBMA clinical manifestations; all patients had small or large nerve fibre neuropathy. Three of five patients had increased neurofilament light levels. Conclusion. The study confirms the systemic involvement in patients suffering from SBMA. Increased NfL concentration was associated with either peripheral neuropathy or decreased body mass index. The complex phenotype of the disease should be kept in mind, as it could help to diagnose patients with SBMA.